Conflicting Blackness in Predator 2 - Łukasz Muniowski (European Journal of American Studies)
The movie Predator 2 (1990) came out just two years before the L.A. Riots, and its depiction of Los Angeles as a war zone stems from the tensions within the city in the 1980s, which culminated in the 1992 riots. This article revisits the movie in the times of Black Lives Matter in order to show how 30 years after its release, it provides a complex, more nuanced picture of race in America of that time. As BLM activists demonstrate, the urban African American is a victim of racial and class profiling. Predator 2 focuses on urban Blackness and law enforcement, and it problematizes the binary oppositions between whiteness and blackness, the police and criminals, etc. The hero of Predator 2 is a Black man and a policeman, so he is a part of the system that creates the oppression of fellow Black men, but he also suffers from it, as he is targeted by his bosses, the FBI, gangsters and, most importantly, the Predator.